Electrochemical behavior of nickel cobalt oxide micro-flowers in different electrolytic systems. (2022) - Siwatch, Poonam; Sharma, Kriti; Tripathi, S.K.
Abstract: Here, nickel cobalt oxide micro-flowers (NCO-F) have been prepared by the hydrothermal method for their application as electrode material in supercapacitors. The electrochemical performance of the prepared material has been studied in three different aqueous electrolytes (1 M Na2 SO4, 1 M KOH, and 1 M Na2 SO4 with hydroquinone (Hq) and benzoquinone (Bq) as redox additives). The NCO-F shows maximum specific capacitance in 1 M KOH (470 Fg −1 ) followed by 1 M Na2 SO4 with Hq and Bq additives (173 Fg −1 ) and 1 M Na2 SO4 (101 Fg −1 ) at the scan rate of 5 mVs −1 . However, the higher value of energy density and power density is obtained in 1 M Na2 SO4 (35.80 Whkg −1 at 424 Wkg −1 ). This is because of the higher potential window possessed by NCO-F in 1 M Na2 SO4 . The results illustrate that the role of the potential window is important which in turn is governed by the type of electrolyte.